Tremor : a novel - Cole, Teju (Random House, 2023)
"Life is hopeless but it is not serious. We have to have danced while we could and, later, to have danced again in the telling. A weekend spent antiquing is shadowed by the colonial atrocities that occurred on that land. A walk at dusk is interrupted by casual racism. A loving marriage is riven by mysterious tensions. And a remarkable cascade of voices speak out from a pulsing metropolis. We're invited to experience these events and others through the eyes and ears of Tunde, a West African man working as a teacher of photography on a renowned New England campus. He is a reader, a listener, a traveler, drawn to many different kinds of stories: stories from history and epic; stories of friends, family, and strangers; stories found in books and films. Together these stories make up his days. In aggregate these days comprise his life. Tremor is a startling work of realism and invention that engages brilliantly with literature, music, race, and history as it examines the passage of time and how we mark it. It is a reckoning with human survival amid "history's own brutality, which refuses symmetries and seldom consoles," but it is also a testament to the possibility of joy. As he did in his magnificent debut, Open City, Teju Cole once again offers narration with all its senses alert, a surprising and deeply essential work from a beacon of contemporary literature." --